Assessing the Efficient Utilization of Electricity by Domestic Consumers in the Agona District (Global Journal of Science Frontier Research, 2015)
The study assessed the efficient utilization of electricity by domestic consumers in the Agona District. Descriptive survey design was employed in the study. Purposive and simple random sampling techniques were used in selecting five (5) towns and 100 respondents, respectively. A questionnaire as well as interview and observation methods were used in data collection. The data obtained from respondents were analyzed using frequencies and percentages. The study revealed that almost two-thirds (63%) of the respondents in the condominium consume electricity from a single central credit meters. Again, the study showed that lack of access to energy efficient technologies have contributed to the waste of electricity in the households. The results also revealed that consumers have little or no knowledge about some basic energy conservation tips. It is recommended that all households in such condominium should be provided with separate meters preferably the pre-paid meters so as to encourage consumers to conserve energy.
Keywords: condominium; credit meters; pre-paid meters; electricity bills